Variability and determinants of total homocysteine concentrations in plasma in an elderly population. - Clarke, R; Woodhouse, P; Ulvik, A; Frost, C; Sherliker, P; Refsum, H; Ueland, P; Khaw, K (1998)
The variability of plasma total homocysteine (tHcy) was examined in 96 individuals over a 1-yr period. Blood tHcy concentrations varied from 7.1 micromol/L in the bottom quintile to 14.5 micromol/L in the top quintile. The mean tHcy was 10.4 micromol/L, the between-person SD was 2.5 micromol/L, and the within-person SD was 0.93 micromol/L. There was little seasonal variation, and the reliability coefficient was 0.88. Mean tHcy concentrations were inversely related to mean plasma folate (r = -0.36) and vitamin B12 (r = -0.35) concentrations. Median tHcy concentrations were approximately 1 micromol/L higher in men than in women and in older (70 to 74 years) than in younger (65 to 69 years) individuals and higher in those with the TT and CT genotypes for the methylenetetrahydrofolate reductase polymorphism than in those with the CC genotype (10.7 and 10.6 vs 9.6 micromol/L). Epidemiological studies based on single tHcy measurements may underestimate the magnitude of any risk associations with disease by 10-15%.